#AskGaryVee one entrepreneur's take on leadership, social media, & self-awareness - Gary Vaynerchuk (New York, NY Harper Business, an imprint of HarperCollinsPublishers, 2016)
An entrepreneur known for The #AskGaryVee Show on YouTube showcases the most useful and interesting questions he has received. Distilling and expanding on the podcast's most urgent and evergreen themes, Gary presents advice on marketing, social media, entrepreneurship, and everything else you've been afraid to ask but are dying to know. Gary gives insights and information on everything from effectively using Twitter to launching a small business, hiring superstars to creating a personal brand, launching products effectively to staying healthy -- and even buying wine.
Includes index.
Keywords: Marketing--Miscellanea.